Pela Navalha - Cotidiano, Moradia e Intimidade. - Spinosa, Vanessa (2005)
The challenge of this work is to discuss the daily life of Belém of Para in the 30´s and also the urban growing of the city that was appearing between changes and permanence. This research intends to contribute for Amazon regional historiography and also discuss about daily life, family, sensibilities, urbanity and popular way of life. Thus, the research has focused crime process of deflower and body lesion among other various historical sources: magazines, memories, albums, statistic boards. This rich and diverse documental framework was able to investigate different dimensions of popular way of life in Belém, their stile of life, their residences, their intimacy, their relationships and feelings. Therefore, historical agents and their residences places were emphasized, especially those who lives in pensions, tenement house, giving a especial attention to details of intimate spaces and the straight relations between it and the dwellers. The neighborhood was another essential point of the analyzes, seeking the comprehension of personal relationship, such as assistance and solidarity, vigilance and interferences, tensions and love affair among different agents with different jobs, such as public functionary, homemaker and stevedore. In additions to this, the research tried to raise questions of sensibility, discussing behaviors, love and affective choices, and how conjugal relationship used to happen among common people. The ideals of marriage and the concubinage were explained, giving evidence to how love and conjugal choices were made, and also how were consolidated the multiples ways of familiar constitutions, some more related to the living together and others related to the choices that were legitimated by the society and by those social agents that where close to them.